The Heart of Seminary Life: An In-Depth Exploration of Integrating Spirituality into All Aspects of Seminary Formation - Giangan, Bernie; Laranjo, Juniel; Selgas, Jinggle (Jurnal Studi Agama, 2025)
The study examines how spiritual formation is integrated into various aspects of seminary formation, which leads to answer the main question "How do the Holy Infant Seminarians integrate spiritual formation to the different aspects of seminary formation?" , using a qualitative single case study of the Holy Infant Seminary. It highlights that communal prayers, adoration of the Blessed Sacrament, and Eucharistic celebrations are key seminary structures that support the spiritual growth of seminarians. Additionally, personal prayer, meditation, journal writing, and reading spiritual books nurture both their spirituality and intellectual development. These practices also enhance their human formation, offering opportunities for self-reflection. The study concludes that integrating spiritual practices into both the seminary’s structures and seminarians’ personal lives is essential for the holistic development of seminarians.